SYNTHESIS AND CHARACTERIZATION OF NEW THERMALLY STABLE POLYAMIDES BASED ON 2,5-PYRIDINE DICARBOXYLIC ACID AND AROMATIC DIAMINES - FAGHIHI,KHALIL (Sociedad Chilena de Química, 2009)
Six new thermally stable polyamides 3a-f were synthesized through the polycondensation reaction of 2,5-pyridine dicarboxylic acid 1 with six different derivatives of aromatic diamines 2a-f in amedium consisting of N-methyl-2-pyrrolidone, triphenyl phosphite, calcium chloride and pyridine. The polycondensation reaction produced a series of novel polyamides containing pyridyl moieties in the main chain in high yield with inherent viscosities between 0.50-0.82 dL/g. The resulting polymers were fully characterized by means of FT-IR spectroscopy, elemental analyses, inherent viscosimetry, and solubility tests. Thermal properties of these polymers were investigated by using thermal gravimetric analysis (TGA) and differantional thermal gravimetry (DTG). All of the polymers were soluble at room temperature in polar solvents such as N,N'-dimethyl acetamide, N,N'-dimethyl formamide, dimethyl sulfoxide and N-methy1-2-pyrrolidone.